Digital game for the development of classroom verbal interaction strategies: enhanced pre-service teacher training model with technology (Juego digital para el desarrollo de estrategias de interacción verbal en aula: modelo de formación inicial de profesores mejorado con tecnología). Issue 3 (2nd July 2020) - López-Neira, Leonardo; Labbé, Christian; Villalta, Marco
ABSTRACT: This article presents the results of the implementation of a training model to develop classroom verbal interaction strategies for student teachers, combining traditional lessons (face-to-face) with a digital game. The research design was pre-experimental with a pre- and post-test which evaluated improvements in the participants' ability to recognize, analyse and design classroom verbal interaction strategies. The sample was comprised of 124 students at two Chilean universities: one public and one private. After five weeks of implementation, the students' ability to recognize, analyse and design classroom verbal interactions increased significantly, with statistically significant differences by university and specialization but not by sex or socioeconomic level. Noteworthy is a positive relationship between the use of the game outside class and the ability to analyse and design classroom interactions. The students very positively evaluated the training module. The implications are analysed, and suggestions are provided to strengthen pre-service teacher training by taking advantage of the opportunities afforded by the digital technologies.